Special pre-competitive conditioning model for elite swimmers - Yakovlev, B. P.; Babushkin, G. D.; Rybin, R. E.; Babushkin, E. G.; Tarasenko, I. B. (Theory and Practice of Physical Culture, 2018)
The study was designed to develop and test by an experiment a pre-competitive conditioning model for elite swimmers to improve their competitive performance. One of the ways to improve the performance, as we believe, is to advance the pre-competitive training of the elite sprint swimmers with a special emphasis on the special tools to prevent the unfavorable mental and physical conditions and reach the optimal prestart mindset and fitness for the competitive success. The pre-competitive conditioning process was improved by the microcycle-specific training scope and intensity control tools. The new pre-competitive conditioning model was practically tested in two competitions and proved beneficial as verified by the progress and success of the Experimental Group in the competitions. The new pre-competitive conditioning model tests give the grounds to recommend it for application in the swimmers` training systems.